2013
DOI: 10.5527/wjn.v2.i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistulas and digital hypoperfusion ischemic syndrome in patients on hemodialysis

Abstract: AIM:To determine survival parameters as well as characteristics of patients with this syndrome. METHODS:The investigation was conducted over a period of eight years, as a prospective, non-randomized, clinical study which included 204 patients, treated by chronic hemodialysis. Most patients received hemodialysis 12 h per week. As vascular access for hemodialysis all subjects had an arteriovenous fistulae. Based on surveys the respondents were divided into groups of patients with and without digital hypoperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
(29 reference statements)
1
8
3
Order By: Relevance
“…Comorbidities such as diabetes (especially insulindependent), coronary artery disease and peripheral arteriopathy are all linked to accelerated atherosclerosis and subsequently are prone to developing ischemia symptoms when blood flow is altered as it is the case of an arteriovenous anastomosis (3,5,21). Our study confirmed coronary artery disease and arteriopathy as risk factors for developing DHIS.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Comorbidities such as diabetes (especially insulindependent), coronary artery disease and peripheral arteriopathy are all linked to accelerated atherosclerosis and subsequently are prone to developing ischemia symptoms when blood flow is altered as it is the case of an arteriovenous anastomosis (3,5,21). Our study confirmed coronary artery disease and arteriopathy as risk factors for developing DHIS.…”
Section: Discussionsupporting
confidence: 72%
“…Lazarides et al (19) retrospectively studied 69 patients with AVF and proved that in 94% of cases a degree of hypoperfusion syndrome exists distal to the fistula as differences in blood pressure were found between the arm bearing the fistula and the controlateral one. However, clinically manifest DHIS will develop only in 8% of patients as compensatory mechanisms (arterial collaterals and distal vasodilatation) improve tissue perfusion (3). Other studies have shown that a surgical procedure is necessary in 1,7% -9% of patients (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in patients undergoing maintenance HD treatment the higher basal serum MPO was associated with inflammation, advanced atherosclerosis, and poorer prognosis [ 44 , 46 ]. On the other hand, basal serum MPO activity in HD patients was in several studies within the range of healthy controls [ 47 , 48 ], except in cases with arteriovenous fistula thrombosis [ 49 ]. These discrepant results probably reflect many confounding factors, such as the duration of HD treatment, use of different dialysis membranes/reuse of a dialyzer, different proportion of underlying causes of CKD, MPO genetic polymorphisms, comorbidities, vitamin, mineral, and antioxidant supplementation, and lipid lowering drugs.…”
Section: Mpo and Renal Replacement Therapy In Ckdmentioning
confidence: 99%
“…Our experience with creation of arteriovenous fistulas for hemodialysis by transposition of veins, shows that there are still are many dilemmas and complications, which should be taken into consideration before deciding on this type of vascular access [6,7,8]. …”
Section: Figure 2 Transposition Basilic Vein In the Forearm Area Veimentioning
confidence: 99%